BETWEEN COMMITMENT AND REALITY – GENDER GAP IN SOCIALLY RESPONSIBLE FRANCHISE COMPANIES IN THE USA AND THE REPUBLIC OF SERBIA - Đurić Kuzmanović, Tatjana; Stanković, Milica S (Poslovna ekonomija, 2017)
The paper is based on the definition of corporate social responsibility (CSR) as a concept that includes a gender-sensitive attitude towards employees. The authors present the historical development of corporate social responsibility concepts and recognize their diversity in modern conditions. The paper examines the gender gap in selected socially responsible companies in the United States and the Republic of Serbia, with a focus on the situation in the franchise sector, with respect to their declared commitments and recommended measures towards employees in the case of gender balance in management and leadership roles. The gender analysis of corporate social responsibility concepts formulated over the past decade confirms their strong gender blindness, and indicates a visible gap between modern declared socially responsible corporate commitments and measures on gender equality and equity interests in business and social practice. The recognized gender gap in the selected franchise companies highlights the need to consistently integrate a gender-sensitive approach in modern business strategy on corporate social responsibility, and the introduction of additional mandatory incentive measures for the promotion of gender equality in socially responsible and business management.